2014
DOI: 10.1007/s10530-014-0832-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential ecological impacts of invader and native predatory freshwater amphipods under environmental change are revealed by comparative functional responses

Abstract: Predicting the ecological impacts of damaging invasive species under relevant environmental contexts is a major challenge, for which comparative functional responses (the relationship between resource availability and consumer uptake rate) have great potential. Here, the functional responses of Gammarus pulex, an ecologically damaging invader in freshwaters in Ireland and other islands, were compared with those of a native trophic equivalent Gammarus duebeni celticus. Experiments were conducted at two dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 62 publications
(85 reference statements)
2
38
0
Order By: Relevance
“…Alexander et al 2014a, b;Dick et al 2013Dick et al , 2017Paterson et al 2014;Laverty et al 2015;Xu et al 2016) have shown that the comparative FR methodology is rapid, efficient and effective at explaining and predicting the ecological damage caused by invasive species. However, in some cases the FR of invasive species is unremarkable when compared to those of native species, yet ecological damage is known to occur, as is the case with N. melanostomus and P. parva toward invaded communities (Barton et al 2005;Britton et al 2010;Gozlan et al 2010;Pagnucco and Ricciardi 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexander et al 2014a, b;Dick et al 2013Dick et al , 2017Paterson et al 2014;Laverty et al 2015;Xu et al 2016) have shown that the comparative FR methodology is rapid, efficient and effective at explaining and predicting the ecological damage caused by invasive species. However, in some cases the FR of invasive species is unremarkable when compared to those of native species, yet ecological damage is known to occur, as is the case with N. melanostomus and P. parva toward invaded communities (Barton et al 2005;Britton et al 2010;Gozlan et al 2010;Pagnucco and Ricciardi 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Fish species were housed separately in opaque plastic tanks (94 cm 9 63 cm 9 50 cm) filled with 120 L of continually aerated dechlorinated tapwater, and were maintained on a diet of frozen chironomid larvae obtained from a commercial fish supplier to standardise prior experience with the prey species being tested (see Laverty et al 2015). Prey species were held separately in glass tanks (35 cm 9 26 cm 9 21 cm) filled with 8L of continually aerated dechlorinated tapwater; stream flora and fauna were added to provide food and habitat.…”
Section: Speciesmentioning
confidence: 99%
“…Prediction of consumer impact has been assessed through the use of comparative functional response analyses (Smout et al 2010;Alexander et al 2012;Alexander et al 2013;Dick et al 2013;Dick et al 2014;Laverty et al 2014;Wasserman et al 2016a, b;Dick et al 2017). This method has been pioneered for the prediction of invasive species impacts in comparison to trophically analogous native species Paterson et al 2015;Dick et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, consideration of changes or differences in the physical environment, such as habitat complexity and water chemistry, can allow impact prediction, owing to shifts in the shape and magnitude of functional responses under such context-dependencies (e.g. Alexander et al 2015;Laverty et al 2015). Whilst not all potential contexts and their interactions can be captured in such studies, those identified as the most relevant can be, and this approach has facilitated the development of general ecological impact models with functional responses at their core (e.g.…”
mentioning
confidence: 99%
“…For example, we do not explicitly relate functional responses to resource competition between the invader and native trophic comparator. This is because displacement of a native by an invader may be driven by interactions other than competition; for example, while the invasive amphipod Gammarus pulex has higher functional responses towards shared prey than the native G. duebeni celticus which is displaced (Laverty et al 2015), it is intraguild predation rather than competition that drives this replacement process (Dick 2008). The higher functional responses of the invader correlates with its impact on the broader ecological community, which might invoke interspecific competition, but this is not explicit in the functional response studies to date.…”
mentioning
confidence: 99%